Proving the Criminal Act of Bullying Committed Children in Cyberspace - Akbar Fadriwansyah (Journal of Legal and Cultural Analytics, 2023)
The purpose of this study is 1) to find out and analyze the method of proving the crime of bullying committed by children in cyberspace. 2) to find out and analyze the validity of the statements of victims of criminal acts of bullying in cyberspace. The research results obtained first; the method of proving the crime of bullying committed by children in cyberspace, because this is related to cyberspace problems in the form of internet media, the method that can be carried out by a judge is based on Law no. 11 of 2008 concerning Information and Electronic Transactions or the ITE Law. This law finally includes electronic information, or electronic documents, or printouts as legal evidence in accordance with the procedural law in force in Indonesia. Second; the validity of the statements of parents of victims of criminal acts of bullying in cyberspace because seen from the Criminal Procedure Code it also stipulates that parties whose statements cannot be heard as witnesses and can resign as witnesses are the defendant or co-defendant, mother's or father's brother, also those who are related by marriage with the children of the defendant's relatives up to the third degree.